2010
DOI: 10.1155/2010/682504
|View full text |Cite
|
Sign up to set email alerts
|

Hypermethylation of SOX2 Promoter in Endometrial Carcinogenesis

Abstract: This paper aimed at investigating the expression and methylation profiles of SOX2, a gene coding for the stem cell-related transcription factor SOX2, in endometrial carcinomas. By methylation-specific polymerase chain reaction (MS-PCR), the methylation status of SOX2 promoter region in 72 endometrial carcinomas and 12 normal endometrial samples was examined. Methylated allele was found in 37.5% (27/72) of endometrial carcinomas but only in 8.3% (1/12) of normal endometrial, significantly more frequent in cance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
16
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 34 publications
3
16
0
Order By: Relevance
“… 1 References: apc (Richiardi et al, 2013; Heller et al, 2010; Hernandez-Vargas et al, 2010); bdnf (D’Addario et al, 2012; Fuchikami et al, 2011; Keller et al, 2010; Autry and Monteggia, 2009); brca1 (Esteller et al, 2000; Esteller et al, 2001; Xu et al, 2009); cdh2 (Berx and van Roy 2009; Sui et al, 2012; Loo et al, 2010); cdkn1a (Campion et al, 2009); c-fos (Liu et al, 2003; Wainfan and Poirier, 1992); cyp1b1 (DiNardo et al, 2013; Habano et al, 2009; Sissung et al, 2006; Tokizane et al, 2005); dazl (Li et al, 2013; Krausz et al, 2012; Navarro-Costa et al, 2010); drd2l (Abdolmaleky et al, 2005); esr1 (Majumdar et al, 2011; Campion et al, 2009); gstp1 (Richiardi et al, 2013; Muggerud et al, 2010); h-ras (Hass et al, 1993; Campion et al, 2009); mlh1 (Muggerud et al, 2010; Heller et al, 2010; Esteller et al, 2001); msh3 (Lahtz and Pfeifer, 2011); nos2b (Breton et al, 2012); nqo1 (Tada et al, 2005); nrf2 (Khor et al, 2011; Yu et al, 2010); p53 (Intarasunanont et al, 2012; Zeng et al, 2011; Hernandez-Vargas et al, 2010; Campion et al, 2009); pten (Campion et al, 2009; Muggerud et al, 2010); sox2 (Farthing et al, 2008; Wong et al, 2010; Hirabayashi and Gotoh, 2010); sox3 (Hirabayashi Gotoh, 2010). …”
Section: Figurementioning
confidence: 99%
“… 1 References: apc (Richiardi et al, 2013; Heller et al, 2010; Hernandez-Vargas et al, 2010); bdnf (D’Addario et al, 2012; Fuchikami et al, 2011; Keller et al, 2010; Autry and Monteggia, 2009); brca1 (Esteller et al, 2000; Esteller et al, 2001; Xu et al, 2009); cdh2 (Berx and van Roy 2009; Sui et al, 2012; Loo et al, 2010); cdkn1a (Campion et al, 2009); c-fos (Liu et al, 2003; Wainfan and Poirier, 1992); cyp1b1 (DiNardo et al, 2013; Habano et al, 2009; Sissung et al, 2006; Tokizane et al, 2005); dazl (Li et al, 2013; Krausz et al, 2012; Navarro-Costa et al, 2010); drd2l (Abdolmaleky et al, 2005); esr1 (Majumdar et al, 2011; Campion et al, 2009); gstp1 (Richiardi et al, 2013; Muggerud et al, 2010); h-ras (Hass et al, 1993; Campion et al, 2009); mlh1 (Muggerud et al, 2010; Heller et al, 2010; Esteller et al, 2001); msh3 (Lahtz and Pfeifer, 2011); nos2b (Breton et al, 2012); nqo1 (Tada et al, 2005); nrf2 (Khor et al, 2011; Yu et al, 2010); p53 (Intarasunanont et al, 2012; Zeng et al, 2011; Hernandez-Vargas et al, 2010; Campion et al, 2009); pten (Campion et al, 2009; Muggerud et al, 2010); sox2 (Farthing et al, 2008; Wong et al, 2010; Hirabayashi and Gotoh, 2010); sox3 (Hirabayashi Gotoh, 2010). …”
Section: Figurementioning
confidence: 99%
“…In most types of cancers, SOX2 acts as an oncogenic transcriptional factor, and thus it may become a novel therapeutic target in these cancers . However, the roles of SOX2 in endometrial cancer are still unclear …”
mentioning
confidence: 99%
“…High expression level of SOX2 in tissues was also associated with poorer outcomes of patients with advanced-stage EC 11 . In contrast, Wong et al 58 proposed that SOX2 was a tumor suppressor gene inhibiting the progression of EC, and low level of it was identified as an indicator of type II serous, clear cell adenocarcinoma as well as shorter survival. These phenomena suggested that further exploration of the molecular mechanisms of SOX2 should be carried out in relation to clinical management of EC.…”
Section: Sox Genes In Gcsmentioning
confidence: 94%
“…Overexpression of SOX2 in cells promoted cell proliferation by inhibiting expression of p21 11 , while low level of SOX2 in tissues caused by promoter hyper-methylation was conversely accompanied by initiation of EC 58 . These phenomena reflecting the role of SOX2 as a biomarker of clinical features in patients with EC was possibly due to different locations of SOX2 and its currently unclear mechanisms.…”
Section: Sox Genes In Gcsmentioning
confidence: 97%
See 1 more Smart Citation